Evaluation of vestibular functions in otosclerosis before and after small fenestra stapedotomy - Panda, Naresh K. (Springer India, 2001)
Vestibular functions in twenty-five patients with otosclerosis were analyzed before and after undergoing stapes surgery. Vertigo was present preoperatively in 6 patients, which disappeared completely after 4–6 weeks of surgery in all the patients indicating the usefulness of stapedectomy. Patients with otosclerosis demonstrated hypoexcitability compared to controls, which was statistically significant for right cold and hot irrigation. Our results showed equal culoric abnormalities in patients with mixed hearing loss and conductive loss. Patients with obliterative focus at surgery had impaired vestibular functions compared to non-obliterative foci without any statistical significance. A longer piston used at surgery tends to produce more vestibular damage compared to a smaller piston. Finally, the degree of vestibular dysfunction seems to be inversely proportional to the hearing result.